1978
DOI: 10.1177/104225877800300203
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Small Manufacturers to the Energy Environment — an Exploratory Study

Abstract: This research examines the impact of the severe energy/weather conditions during the Winter 1976–77 on smaller manufacturers in Western Pennsylvania. It was found that size of firm, energy intensity and extent of energy curtailment were not related (statistically) to the kind and extent of firms' energy conservation programs and/or the nature of the managerial response to the above mentioned conditions. The sample firms had made few major commitments to improve energy efficiency. Lack of capital resources and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some sources report that numerous entrepreneurs perceive that social responsibility activities may endanger the financial security of their firms (Besser & Miller, 2004). Researchers have uncovered some evidence to the effect that entrepreneurs are less committed than larger corporate firms in fields such as energy conservation (Doctors, Fahey, & Patton, 1978). Overall, considering the various indirect research and pragmatic evidence, it might be expected that entrepreneurs are not likely to be highly involved in the social responsibility area (Jay & Thum, 2005;Peters, 1996;Rosen, Hall, & Stainer, 2005).…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some sources report that numerous entrepreneurs perceive that social responsibility activities may endanger the financial security of their firms (Besser & Miller, 2004). Researchers have uncovered some evidence to the effect that entrepreneurs are less committed than larger corporate firms in fields such as energy conservation (Doctors, Fahey, & Patton, 1978). Overall, considering the various indirect research and pragmatic evidence, it might be expected that entrepreneurs are not likely to be highly involved in the social responsibility area (Jay & Thum, 2005;Peters, 1996;Rosen, Hall, & Stainer, 2005).…”
Section: Hypothesesmentioning
confidence: 99%
“…Previous studies have indicated that certain demographic and lifestyle variables considerably diverge from one entrepreneur to another and that these variables are predictive of the decision making and associated behavior of entrepreneurs (Doctors et al, 1978). Thus, it appears to be appropriate to evaluate the relationship of these variables to dedication to social responsibility.…”
Section: Hypothesesmentioning
confidence: 99%